Customer Satisfaction with the Goods and Services Offered By MYDIN - Muhammad Hafiz Bin Mohd Nazri; Daisy Mui Hung Kee; Muhammad Azamuddin Bin Abd Wahab; Aiman Bin Subli; Mohamad Afreza bin Mohd Azmi; Suvin Varghese; Tanya Sinha (AIBPM Publisher, 2020)
Customer Satisfaction can be described as the fulfilment that customers obtain from doing business with a firm. In simpler terms, it’s how pleasant the customers transaction and overall experience with the company was. Customers obtain satisfaction when their needs are met on consuming a product or a service effortlessly, which being more convenient makes them loyal to the firm. Hence, customer loyalty can be easily gained through satisfaction of customers. In our investigation, we focus on the customer satisfaction with the goods and services offered by MYDIN at Bukit Jambul Complex, Bayan Lepas, Pulau Pinang. We have referred to marketing mix such as product, place, promotion and price to measure customer satisfaction. To obtain information and data on customer satisfaction, we conducted a survey to MYDIN and interviewed some of its customers and employees. The result of the study indicate that the methods used are very effective in measuring customer satisfaction.